2014
DOI: 10.1245/s10434-014-3629-2
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Expression Shows Distinctive Significance in ER Positive and Negative Breast Cancers

Abstract: AR expression was different in ER+ and ER- cancers and had different clinical implications. AR alone may not be a good marker for MA subtype. Its expression in MA may have substantial prognostic implication and as such warrants further validation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(61 citation statements)
references
References 37 publications
6
52
2
1
Order By: Relevance
“…28 AR AR is a steroid nuclear receptor and is expressed more frequently than ER in breast cancer. 63 Although the precise role of AR in breast carcinogenesis is not clear, the possibility of it serving as a therapeutic target, especially in TNBC, is of significant interest. 35 Clinically, AR positivity is associated with better prognosis and, more recently, 21 associated with a lower recurrence score using the 21-gene test.…”
Section: Ck5/6mentioning
confidence: 99%
“…28 AR AR is a steroid nuclear receptor and is expressed more frequently than ER in breast cancer. 63 Although the precise role of AR in breast carcinogenesis is not clear, the possibility of it serving as a therapeutic target, especially in TNBC, is of significant interest. 35 Clinically, AR positivity is associated with better prognosis and, more recently, 21 associated with a lower recurrence score using the 21-gene test.…”
Section: Ck5/6mentioning
confidence: 99%
“…The vast majority of ERa-and PR-positive breast cancers also express AR (Ogawa et al 2008, Park et al 2011, Alshenawy 2012, Secreto et al 2012, Santagata et al 2014, Sultana et al 2014, Tsang et al 2014, and AR expression is observed in up to 50% of ERa-and/or PR-negative breast cancers (Gucalp et al (2013), Tsang et al (2014); reviewed in Hickey et al (2012), McNamara et al (2013) and Nahleh (2008)), making AR an attractive target for the treatment of multiple types of breast cancer. However, it is currently unclear how to stratify individual breast cancers based on whether they will respond favourably to androgen treatment or not.…”
Section: Ar Expression In Mammary Epitheliummentioning
confidence: 99%
“…This is somewhat remarkable, particularly with respect to the breast, as it has long been known that androgen hormones inhibit pubertal and post-pubertal breast growth, and that treatment with androgen can cause regression of breast tumours (Lamar & Rezek 1958, Thomas et al 1962, Tormey et al 1983, Forsbach et al 2000, Rose et al 2000. Indeed, AR is the most frequently expressed sex steroid receptor in both primary and secondary (metastatic) breast cancers, making it a highly prevalent therapeutic target (McNamara et al 2013, Santagata et al 2014, Tsang et al 2014. We have recently reviewed the role of AR signalling in normal and malignant breast tissues (Hickey et al 2012), and McNamara et al (2013) provide an update on that theme in this issue including a section on intracrine androgen metabolism in the breast and the implication of this for AR signalling in breast cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Immunohistochemical studies have demonstrated that AR expression varies between the different subtypes, with a higher positivity in luminal A-like tumours and a lower positivity in TNBCs (Luo et al 2010, Park et al 2010, Loibl et al 2011, Tsang et al 2014. A number of studies have investigated the prognostic potential of AR expression in BCs, with the majority finding the AR to be associated with favourable clinicopathological features.…”
Section: Ar As a Prognostic Factormentioning
confidence: 99%
“…A number of studies have investigated the prognostic potential of AR expression in BCs, with the majority finding the AR to be associated with favourable clinicopathological features. In ERa-positive BCs, AR has been found to correlate with lower grade, reduced lymph node involvement and longer disease-free survival, and this correlation is proportional to the levels of AR expression (Schippinger et al 2006, Søiland et al 2008, Castellano et al 2010, Hu et al 2011, Park et al 2011, Tsang et al 2014. In one study, AR and ERa levels were analysed in 1467 BC tumours from postmenopausal women enrolled in the Nurses' Health Study (Hu et al 2011).…”
Section: Ar As a Prognostic Factormentioning
confidence: 99%